2015
DOI: 10.1007/s00392-015-0820-9
|View full text |Cite
|
Sign up to set email alerts
|

Higher plasma levels of MR-pro-atrial natriuretic peptide are linked to less anxiety: results from the observational DIAST-CHF study

Abstract: In our study population of outpatients with cardiovascular risk factors, plasma concentrations of MR-proANP were negatively and independently related to clinically relevant anxiety. Further investigations are required to search for possible anxiolytic effects of this circulating natriuretic peptide in medical outpatients with cardiovascular risk factors for diastolic dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 42 publications
2
10
0
Order By: Relevance
“…Midregion pro-atrial natriuretic peptide (MR-proANP) is closely related to NT-proBNP, and both are released by cardiac myocytes to promote diuresis and vasodilation. These natriuretic peptides also demonstrate anxiolytic behavior, whereas both animal and human studies suggest that these natriuretic peptides partially suppress the HPA axis (12)(13)(14)(15). C-terminal proendothelin-1 (CT-proET) is a vasoconstrictor produced by endothelial and vascular smooth muscle cells and can increase proinflammatory cytokine levels such as interleukins (interleukin-1 and interleukin-1 receptor antagonist [IL-1Ra]) (16,17).…”
Section: Introductionmentioning
confidence: 98%
“…Midregion pro-atrial natriuretic peptide (MR-proANP) is closely related to NT-proBNP, and both are released by cardiac myocytes to promote diuresis and vasodilation. These natriuretic peptides also demonstrate anxiolytic behavior, whereas both animal and human studies suggest that these natriuretic peptides partially suppress the HPA axis (12)(13)(14)(15). C-terminal proendothelin-1 (CT-proET) is a vasoconstrictor produced by endothelial and vascular smooth muscle cells and can increase proinflammatory cytokine levels such as interleukins (interleukin-1 and interleukin-1 receptor antagonist [IL-1Ra]) (16,17).…”
Section: Introductionmentioning
confidence: 98%
“…Studies examining the impact of GAD on cardiovascular prognosis have yielded conflicting results: On one hand, GAD has been identified as an etiological risk factor of adverse cardiovascular events [11] such as ischemic stroke [12], myocardial infarction [13,9]. On the other hand, recently several large scale studies show that GAD patients had a better prognosis following a cardiac event [14][15][16][17]. A probable reason for this positive effect of GAD might be due to higher alertness and increased health promoting behavior [15].…”
Section: Introductionmentioning
confidence: 99%
“…Since we previously observed an inverse association of natriuretic peptides and CT-proAVP with anxiety in the same cohort, we additionally controlled for natriuretic peptides and CT-proAVP in the present analysis [ 14 , 16 ]. N-terminal pro-brain natriuretic peptide (NT-proBNP) was measured with a non-competitive electro-chemiluminescence immunoassay (Elecsys, Roche Diagnostics, Mannheim, Germany) using a monoclonal biotinylated NT-proBNP antibody directed against amino acids 1–21 and a secondary monoclonal antibody conjugated to a ruthenium complex binding to amino acids 39–50 [ 40 , 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…While only two observational studies reported a protective effect of anxiety on mortality in patients with coronary heart disease, numerous studies demonstrated that anxiety disorders are associated with increased mortality and worse prognosis [1][2][3][4][5][6][7][8]. In patients with heart disease, several parameters of neuroendocrine activation and inflammation have been found increased and some of these markers, such as natriuretic peptides or C-terminal pro-arginine vasopressin (CT-proAVP), have been proposed to elicit anxiolytic effects [9][10][11][12][13][14][15][16]. Galectin-3 has been introduced as another prognostic biomarker for increased mortality risk in heart failure [17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%